AGAMA DAN KELOMPOK MINORITAS: KASUS LGBT - Surianti Surianti (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2021)
In the context of belief, each religion equally teaches the Oneness of God and in social matters it also teaches goodness such as doing good to fellow religions and inter-religious people. But this does not rule out the possibility that their perspective on cases in social reality has differences, one of which is in terms of sexuality in the LGBT minority group who often gets discriminated against from the public, because they are influenced by many biased thoughts and views that lead to misunderstandings. There are many factors behind a person becoming LGBT including environmental factors, sexual freedom, genetics, hormones, rationale justification and also the principles of life so that it can be understood that LGBT is not necessarily formed without the involvement of other people in it. The counseling process is one of the key points that can be used as a treatment for this problem, with a behavioral approach expected to be able to change LGBT behavior to adapt well to their living conditions.